Paternal High Fat Diet and Exercise Differentially Regulate Placental Development and Inflammation in a Sex-Specific Manner in C57BL6/J Mice (P19-003-19). (13th June 2019) - Larson, Kate; Bundy, Amy; Alvine, Travis; Roemmich, James
Abstract: Objectives: We have shown that increases in T2D risk in male offspring when the father consumes a high-fat (HF) diet can be normalized when the father also exercises during preconception, and that this protection may occur by epigenetic increases in insulin signaling within offspring skeletal muscle. In our current study, we investigated to determine how paternal HF diet and exercise conditions alter sperm miRNA, fetal weight and placental inflammation. Methods: Three-week old male C57BL/6 mice were fed a normal-fat (NF) diet (16% fat) or a HF diet (45% fat) and assigned to either voluntary wheel running exercise or cage activity for 3 months prior to mating with NF diet fed dams. Sperm samples were collected to determine changes in miRNA that may account for the enhanced offspring skeletal muscle responses that helped normalize paternal HF-induced glucose intolerance. Placentae were collected to determine whether changes in sperm miRNA expression differed by amount of placental inflammation. Results: Sperm expression of miRNA 193b increased with paternal HF and exercise. In F1 males, placental and fetal weight decreased with HF diet while, in F1 female, paternal HF and exercise had no effect on placental and fetal weights. Paternal HF diet decreased placental IL-6 and TNF-alpha mRNA expression in F1 females, while no effects were observed in F1 male placenta. Conclusions: Taken together these data suggest that paternal HF diet has a greater impact on placental development of male fetuses while paternal exercise has greater impact on placental inflammation of female fetuses. For both female and male fetuses, these paternal influences are mediated via sperm miRNA 193b. miR-193b is involved in regulation of the cell cycle and adipogenesis but may have additional functions. Thus, the exact role of sperm miRNA 193b in sex-specific epigenetic transmission of paternal HF diet and exercise on placental and fetal development needs further evaluation. Funding Sources: USDA Agricultural Research Service Project #3062-51000-052-00D.